Development Of Hemicelluloses Biodegradable Films From Oil Palm Frond (Elais Guineensis). - Ariffin, Fazilah; Mohd Noor, Azemi; A.H, Noor Haliza (2006)
Biodegradable films were developed from hemicelluloses of oil palm fronds (OPF) extracted using alkali extraction method. The effects of different alkali [Potassium Hydroxide (KOH)] concentrations (1.0, 2.0, 3.0M) on the film properties [Thickness, color, mechanical, solubility, and water vapor transfer rate (WVTR)] of the films were investigated. The hemicelluloses yields were found to be increased with the increase in concentration with all the extracts produced self-supporting films. Film thickness ranged from 0.13-0.14 mm. Measured data for the hemicelluloses films were 11-15 MPa tensile strength, 1-3 % elongation, 64-93% solubility in water, and 180-210 g m,2 d'] water vapor transfer rate (WVTR). This study suggests that OPF has a good potential in obtaining hemicelluloses for production of biodegradable film for certain application. Keywords Biodegradable film, hemicelluloses, oil palm frond, alkali extraction